TRANSFORMASI HUKUM NASIONAL DALAM ERA GLOBALISASI DIGITAL DAN EKONOMI BERBASIS PLATFORM - Althea Serafim Kriswandaru (Judge : Jurnal Hukum, 2026)
This study emerges as a response to the phenomenon of digital globalization and the growth of the platform-based economy, which has brought significant changes to the national legal framework. The development of information technology, the emergence of e-commerce, fintech, and other digital services have created new challenges for the legal system, including consumer protection, intellectual property rights, data security, and the regulation of electronic contracts. In this context, the government and legal institutions need to adjust regulations so that they remain relevant and capable of effectively governing digital economic activities. The objective of this study is to analyze how national law adapts to these changes, identify the obstacles that arise, and evaluate the effectiveness of the regulations implemented. The research employs a qualitative approach, with data collected through in-depth interviews with legal experts, regulators, and digital economy practitioners, as well as through the analysis of relevant regulatory and policy documents. The collected data were analyzed thematically to describe the dynamics of legal transformation and its impact on platform-based economic practices. The findings indicate that national law has undergone significant adaptation, including the revision of legislation, the implementation of digital regulations, and the strengthening of consumer rights protection. However, several challenges remain, such as gaps in implementation in practice, cross-jurisdictional complexities, and the need to synchronize new regulations with the existing legal system. The discussion emphasizes that the success of legal transformation largely depends on the readiness of legal institutions, the adaptability of legislative processes, and collaboration between the public and private sectors. Therefore, the transformation of national law in the era of digitalization and the platform economy is a dynamic process that requires stronger regulations, policy harmonization, and education for the public and business actors so that the legal system can function effectively, adaptively, and support equitable growth of the digital economy.